A case of meningitis caused by streptococcus pyogenes in a child with ventriculoperitoneal shunt and Ommaya reservoir [Ventriküloperitoneal şantı ve ommaya rezervuarı olan çocukta streptokokkus pyogenes menenjiti] - BAYRİ, YAŞAR (AVES, 2013)
Streptococcus pyogenes is a well-known cause of invasive infections. However, acute bacterial meningitis caused by this pathogen is unusual. Herein, we presented a child with ventriculoperitoneal (VP) shunt and bilateral ommaya reservoir who developed group A streptococcal (GAS) meningitis a month after the last neurosurgery operation. The patient was treated with removal of VP shunt and ommaya reservoir and antibiotic therapy including vancomycin, ceftriaxone and clindamycin for 21 days. Although many predisposing factors have been described for GAS meningitis, this is the first report of an association between ommaya reservoir and VP shunt due to S. pyogenes meningitis. Clinicans should be aware that sporadic cases can occur and if it is treated promptly, the outcome tends to be favourable. © 2013. 2013 by Pediatric Infectious Diseases Society.
Keywords: Meningitis; Ommaya rezervoir; Streptococcus pyogenes; Ventriculoperitoneal shunt